Polybutyl acrylate, preparation method and ASA resin
By introducing excess double bonds on the polybutyl acrylate molecular chain and performing RAFT polymerization, the problems of low impact strength and complex polymerization process of existing ASA resins are solved, and ASA resins with ultra-high impact strength and excellent weather resistance are prepared, which are suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202411702373.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing ASA resin has low impact strength, complex polymerization process, and insufficient weather resistance of the prepared resin, which limits its application in outdoor and automobile fields.
RAFT reagent is used to introduce excess double bonds on the polybutyl acrylate (PBA) molecular chain to form a rubber structure and is used for grafting of styrene and acrylonitrile to improve the compatibility of the rubber phase and the resin phase, thereby improving the mechanical properties of the resin.
The prepared hyperbranched high molecular weight narrow distribution PBA has high rubber elasticity and toughening effect. The prepared ASA resin has ultra-high impact strength (greater than 400J/m) and excellent weather resistance. It is suitable for home appliances, office supplies, outdoor equipment and automobiles.
Smart Images

Figure BDA0005153662030000121 
Figure BDA0005153662030000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymers and discloses a preparation method and application of polybutyl acrylate (PBA), and specifically relates to a hyperbranched high molecular weight narrow distribution PBA and a preparation method thereof, and an ASA resin prepared therefrom. Background Art
[0002] ASA resin is an engineering plastic with excellent performance. It is grafted copolymerized by three monomers: acrylonitrile, butyl acrylate and styrene. It has a core-shell structure. The polybutyl acrylate rubber phase is the core, which can play a toughening effect and provide impact resistance for the resin. Styrene-acrylonitrile resin (SAN) is the shell, which enhances the compatibility of the dispersed phase and the continuous phase.
[0003] Compared with ABS, ASA resin uses butyl acrylate as the rubber core instead of butadiene. The rubber has no extra double bonds, so it has good weather resistance and is mostly used in outdoor fields such as home appliances, automobiles, and traffic signs. However, there are no extra double bonds in polybutyl acrylate, the toughening effect of polybutyl acrylate rubber is poor, and styrene and acrylonitrile are difficult to graft on the outer layer of the core. The impact strength of ASA resin is low, which limits its application.
[0004] The leading ASA resin manufacturers LG and Benling often add crosslinking agents and grafting agents such as methyl methacrylate, ethylene glycol dimethacrylate, divinylbenzene and diallyl maleate to PBA polymerization to provide crosslinking double bonds and grafting sites. The impact strength of the prepared ASA resin is less than 250J / m. In order to improve the impact strength of ASA resin, it is generally necessary to blend a small particle size of 100nm and a large particle size of 400nm to improve the impact resistance by utilizing the synergistic effect of mixing large and small particle sizes, but this makes the polymerization process and technology more complicated. Most domestic manufacturers choose to increase the impact strength by increasing the amount of ASA rubber powder added, but too much rubber powder will weaken the resin processing performance and increase the difficulty of dispersing the rubber powder in the SAN matrix. The impact strength of ASA resin will decrease instead, and the maximum will not exceed 400J / m.
[0005] In summary, PBA polymerization mostly adopts redox and thermally initiated free radical polymerization. The PBA polymerization process requires the additional addition of crosslinking agents and grafting agents to form a rubber core and a complete grafted shell. The polymerization process is complicated, and the impact strength of the prepared ASA resin is not high. Summary of the invention
[0006] In view of the above problems existing in the prior art, one of the objects of the present invention is to provide a method for preparing polybutyl acrylate, which adopts a RAFT agent to introduce redundant double bonds into the PBA molecular chain on the one hand to make it cross-linked into a rubber structure, and on the other hand to be used for the grafting of styrene and acrylonitrile to increase the compatibility between the rubber phase and the resin phase and improve the mechanical properties of the resin.
[0007] The second object of the present invention is to provide a polybutyl acrylate prepared by the above method, which has a high molecular weight and a narrow molecular weight distribution, and at the same time has a high degree of branching, high rubber elasticity, and better toughening effect.
[0008] The third object of the present invention is to provide an ASA resin prepared from the aforementioned polybutyl acrylate, which has ultra-high impact strength (greater than 400 J / m) and excellent weather resistance (UV aging test 500h, dE less than 15), and can be used in home appliances, office supplies, outdoor equipment and automobiles.
[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0010] In a first aspect, the present invention provides a method for preparing polybutyl acrylate (PBA), comprising the following steps:
[0011] S1: mixing butyl acrylate, RAFT agent, emulsifier, optional electrolyte and water, and then adding initiator and reducing agent to react to obtain PBA seed emulsion;
[0012] S2: mixing butyl acrylate, RAFT agent, emulsifier, initiator and water into a pre-emulsion;
[0013] S3: adding a reducing agent and a pre-emulsion to the PBA seed emulsion to react and prepare polybutyl acrylate.
[0014] In one embodiment of the present invention, based on 100 parts of butyl acrylate added in step S1 and step S2, the raw materials are composed as follows:
[0015] Step S1 comprises: 1-10 parts of butyl acrylate, 0.01-0.5 parts of RAFT agent, 0.003-0.1 parts of emulsifier, 0-1 parts of electrolyte, 50-150 parts of water, 0.01-0.05 parts of initiator, and 0.2-1.5 parts of reducing agent;
[0016] Step S2 comprises: 90-99 parts of butyl acrylate, 5-10 parts of RAFT agent, 0.15-3 parts of emulsifier, 0.1-10 parts of water, and 0.15-3 parts of initiator;
[0017] Step S3 includes: 0.1-10 parts of a reducing agent. Specifically, in step S1, the butyl acrylate includes but is not limited to 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or a range consisting of any two of them;
[0018] The RAST reagent includes but is not limited to 0.01 part, 0.05 part, 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part or a range consisting of any two thereof;
[0019] The emulsifier includes but is not limited to 0.003 parts, 0.005 parts, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.1 parts or a range consisting of any two thereof;
[0020] The electrolyte includes but is not limited to 0 part, 0.001 part, 0.01 part, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part or a range consisting of any two thereof;
[0021] The water includes but is not limited to 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts or a range consisting of any two thereof;
[0022] The initiator includes but is not limited to 0.01 part, 0.015 part, 0.02 part, 0.025 part, 0.03 part, 0.035 part, 0.04 part, 0.045 part, 0.05 part or a range consisting of any two thereof;
[0023] The reducing agent includes, but is not limited to, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.4 parts, 1.5 parts or a range consisting of any two of them.
[0024] Specifically, in step S2: the butyl acrylate includes but is not limited to 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or a range consisting of any two of them;
[0025] The RAST reagent includes but is not limited to 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or a range consisting of any two thereof;
[0026] The emulsifier includes but is not limited to 0.15 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts or a range consisting of any two thereof;
[0027] The water includes but is not limited to 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or a range consisting of any two thereof;
[0028] The initiator includes but is not limited to 0.15 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts or a range consisting of any two of them.
[0029] Specifically, in step S3: the reducing agent includes but is not limited to 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or a range consisting of any two of them.
[0030] In one embodiment of the present invention, the RAFT agent is a reversible addition-fragmentation chain transfer agent having a branched chain structure. Specifically, the RAFT agent is selected from thioester compounds, preferably one or more of Bis-MPA-RAFT dendr imer, pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothiothio)-2-methylpropanoate, 2-((((2-(((dodecylthio)thiothio)thio)thio)-2-methylpropanoyl)oxy)methyl)-2-methylpropane-1,3-diylbis((2-(((dodecylthio)thiocarbonyl)thio)-2-propionic acid methyl ester).
[0031] The preparation method of the present invention also includes conventional auxiliary agents such as emulsifiers, electrolytes, initiators, and reducing agents, which can be conventionally selected in the field and are not particularly required by the present invention.
[0032] In one embodiment of the present invention, the emulsifier is an anionic emulsifier, preferably one or more of potassium oleate, potassium disproportionated rosin acid, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and dioctyl sodium sulfosuccinate.
[0033] In one embodiment of the present invention, the electrolyte is an inorganic salt, preferably one or more of potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, and sodium tripolyphosphate.
[0034] In one embodiment of the present invention, the initiator is selected from inorganic peroxides and / or organic peroxides, preferably one or more of potassium persulfate, sodium persulfate, ammonium persulfate, dicumyl peroxide, and cumyl hydroperoxide.
[0035] In one embodiment of the present invention, the reducing agent is selected from one or more of ferrous sulfate, glucose, sodium pyrophosphate, disodium ethylenediaminetetraacetate, and bleaching agent.
[0036] In one embodiment of the present invention, the reaction in step S1 is carried out at a temperature of 50-80°C and for a time of 0.3-1h; specifically, the temperature includes but is not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two thereof; the time includes but is not limited to 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or a range consisting of any two thereof.
[0037] In one embodiment of the present invention, the pre-emulsion in S3 is added by continuous dripping, and the addition time is 2-5h, including but not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range consisting of any two thereof.
[0038] In one embodiment of the present invention, the reaction in S3 is performed at a temperature of 50-80°C and a time of 0.5-3h; specifically, the temperature includes but is not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two thereof; the time includes but is not limited to 0.5h, 1h, 1.5h, 2h, 2.5h, 3h or a range consisting of any two thereof;
[0039] Specifically, the reaction time starts from the time when the addition of the pre-emulsion is completed.
[0040] In a second aspect, the present invention provides polybutyl acrylate (PBA), which is prepared by the method described above. Specifically, the product prepared by the above method is a PBA latex.
[0041] The polybutyl acrylate of the present invention has the characteristics of high molecular weight, narrow molecular weight distribution and hyperbranching; wherein the molecular weight can be as high as 20w or more; the molecular weight distribution is between 1-1.2;
[0042] The rubber swelling ratio is above 30, indicating a high degree of branching. Since rubber has a three-dimensional network cross-linked structure, the degree of molecular chain branching cannot be directly measured by instruments, but the swelling ratio can be used to characterize the degree of branching.
[0043] In a third aspect, the present invention also provides use of the polybutyl acrylate for preparing ASA resin.
[0044] In one embodiment of the present invention, the ASA resin is prepared by grafting, condensing, dehydrating and drying the polybutyl acrylate latex (PBA) mentioned above with styrene and acrylonitrile to obtain ASA rubber powder, which is then blended with SAN resin and extruded.
[0045] The method for preparing ASA resin from PBA latex is an existing process, wherein the operations of grafting, coagulation, dehydration, drying, blending, extrusion, etc. are all conventional techniques in the art. The relevant operations and process conditions in the preparation method of the present invention, and the devices used therein, can all be carried out by using the corresponding conventional selections in the art, and there is no particular limitation thereto. The technicians can combine and screen and optimize the known processes in the prior art according to actual needs, and the present invention will not repeat them in detail.
[0046] In the present invention, an ASA resin prepared from the above-mentioned polybutyl acrylate has ultra-high impact strength greater than 400 J / m and excellent weather resistance, with a dE less than 15 in a UV aging test of 500 h.
[0047] The ASA resin of the present invention can be applied to the fields of household appliances, office supplies, automobiles, etc., and is particularly suitable for the automobile field.
[0048] As described above, in the method provided by the present invention, a hyperbranched high molecular weight narrow distribution PBA latex is first prepared by RAFT polymerization, and then styrene and acrylonitrile are grafted on the surface of the rubber core to obtain ASA latex, the latex is condensed and powdered, and the ASA rubber powder is blended with SAN resin to obtain ultra-high impact ASA resin. In this method, RAFT is used as a crosslinking agent and a grafting agent to prepare polybutyl acrylate by polymerization, and redundant double bonds are introduced into the PBA molecular chain by the RAFT agent to make it crosslinked into a rubber structure, which can also be used for the grafting of styrene and acrylonitrile, thereby increasing the compatibility between the rubber phase and the resin phase and improving the mechanical properties of the resin.
[0049] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0050] The present invention uses a branched RAFT agent to make PBA polymerization without adding a crosslinking agent and a grafting agent, so that styrene and acrylonitrile can be grafted on the rubber core. The PBA prepared by the RAFT agent participating in the polymerization has an ultra-high molecular weight and a narrow molecular weight distribution. The PBA molecular chain is highly branched, which is conducive to cross-linking to form a three-dimensional network structure, and the PBA rubber has a good toughening effect. A small amount of ASA rubber powder can be used to prepare an ultra-high impact ASA resin. The ASA resin prepared by the method has excellent impact performance, an impact strength greater than 400 J / m, and excellent weather resistance. The ultraviolet aging test is 500h and the dE is less than 15. DETAILED DESCRIPTION
[0051] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0052] The sources of raw materials in the examples and comparative examples of the present invention are as follows. Unless otherwise specified, the raw materials used in the examples or comparative examples are obtained from common commercial channels;
[0053] Butyl acrylate, Wanhua Chemical;
[0054] Sodium lauryl sulfate, 99%, purchased from Aladdin;
[0055] Cumene hydroperoxide, 80%, purchased from Aladdin;
[0056] tert-Butyl hydroperoxide, 70%, purchased from Aladdin;
[0057] Potassium oleate, BM-400, was purchased from Ino Reagent;
[0058] Ferrous sulfate, 99%, purchased from Xilong Chemical;
[0059] Glucose, 99%, purchased from Xilong Chemical;
[0060] Sodium pyrophosphate, 99%, purchased from Aladdin;
[0061] Allyl methacrylate, 99%, purchased from Aladdin;
[0062] n-Octylmercaptan, purchased from Aladdin;
[0063] RAFT reagents were purchased from Sigma.
[0064] Example 1
[0065] 5 parts by weight of butyl acrylate, 0.05 parts by weight of pentaerythritol tetra[2-(dodecylthiocarbonylthiothiothio)-2-methylpropionate reagent, 0.025 parts by weight of sodium dodecyl sulfate, 0.5 parts by weight of sodium carbonate and 100 parts by weight of deionized water were added into a reactor, mixed and kept warm at 70°C, and then 0.025 parts by weight of cumene hydroperoxide and 1 part by weight of ferrous sulfate were added into the reactor, reacted for 0.5h, and a PBA seed emulsion was prepared.
[0066] 95 parts by weight of butyl acrylate, 8 parts by weight of pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothiothio)-2-methylpropionate reagent, 1 part by weight of sodium dodecyl sulfate, 1.5 parts by weight of cumene hydroperoxide and 5 parts by weight of deionized water were mixed to form a pre-emulsion.
[0067] 1 part by weight of ferrous sulfate and 4 parts by weight of glucose were added to the PBA seed emulsion, and then the pre-emulsion was added dropwise thereto for 3 hours, and the mixture was kept at 75° C. for 2 hours to prepare polybutylacrylate latex.
[0068] Example 2
[0069] 10 parts by weight of butyl acrylate, 0.5 parts by weight of Bis-MPA-RAFT dendrimer reagent, 0.1 parts by weight of potassium oleate, 1 parts by weight of potassium carbonate and 150 parts by weight of deionized water were added into a reactor, mixed and kept warm at 80°C, and then 0.05 parts by weight of cumene hydroperoxide, 0.1 parts by weight of ferrous sulfate and 0.1 parts by weight of sodium pyrophosphate were added into the reactor and reacted for 1 hour to prepare a PBA seed emulsion.
[0070] 90 parts by weight of butyl acrylate, 10 parts by weight of Bis-MPA-RAFT dendrimer agent, 3 parts by weight of sodium dodecyl sulfate, 3 parts by weight of tert-butyl hydroperoxide and 10 parts by weight of deionized water were mixed to form a pre-emulsion.
[0071] 0.1 parts by weight of ferrous sulfate was added to the PBA seed emulsion, and then the pre-emulsion was added dropwise thereto for 5 hours. The mixture was kept at 80° C. for 0.5 hours to prepare polybutyl acrylate latex.
[0072] Example 3
[0073] 1 part by weight of butyl acrylate, 0.01 part by weight of 2-((((2-(((dodecylthio)thiothio)thio)-2-methylpropanoyl)oxy)methyl)-2-methylpropane-1,3-diylbis((2-(((dodecylthio)thiocarbonyl)thio)-2-methylpropionate) reagent, 0.003 part by weight of sodium dodecyl sulfate and 50 parts by weight of deionized water were added into a reactor, mixed and kept warm at 50°C, and then 0.01 part by weight of tert-butyl hydroperoxide and 0.2 part by weight of ferrous sulfate, 0.3 part by weight of glucose and 1 part by weight of sodium pyrophosphate were added into the reactor, reacted for 0.3h, and a PBA seed emulsion was prepared.
[0074] 99 parts by weight of butyl acrylate, 5 parts by weight of 2-((((2-(((dodecylthio)thiothio)thio)-2-methylpropanoyl)oxy)methyl)-2-methylpropane-1,3-diylbis((2-(((dodecylthio)thiocarbonyl)thio)-2-propionic acid methyl ester) reagent, 0.15 parts by weight of sodium dodecyl sulfate, 0.15 parts by weight of tert-butyl hydroperoxide and 0.1 parts by weight of deionized water were mixed to form a pre-emulsion.
[0075] 10 parts by weight of glucose was added to the PBA seed emulsion, and then the pre-emulsion was dripped therein for 2 hours, and the mixture was kept at 50° C. for 3 hours to prepare polybutyl acrylate latex.
[0076] Comparative Example 1
[0077] Referring to the method of Example 1, the only difference is that pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothiothio)-2-methylpropionate (RAFT agent) is not used, but is replaced by an equal amount of 4-cyano-4-[[(dodecylthio)thioketonemethyl]thio]pentane, and other operations and conditions are the same as those in Example 1 to prepare polybutyl acrylate latex.
[0078] Comparative Example 2
[0079] Referring to the method of Example 1, the only difference is that pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothiothio)-2-methylpropionate (RAFT agent) is not used, but is replaced by an equal amount of cross-linking agent allyl methacrylate, and other operations and conditions are the same as those in Example 1 to prepare polybutyl acrylate latex.
[0080] Comparative Example 3
[0081] Referring to the method of Example 1, the only difference is that pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothiothio)-2-methylpropionate (RAFT agent) is not used, but is replaced by an equal amount of chain transfer agent n-octyl mercaptan, and other operations and conditions are the same as those in Example 1 to prepare polybutyl acrylate latex.
[0082] PBA latex test example
[0083] The PBA latex prepared in Examples 1-3 and Comparative Examples 1-3 was tested for its performance parameters using the following method. The results are shown in Table 1:
[0084] PBA molecular weight test: PBA is swelled with acetone solvent, filtered to obtain a clear liquid, and the acetone is dried to obtain uncrosslinked PBA. Testing its molecular weight can indirectly characterize the molecular weight of crosslinked PBA rubber.
[0085] PBA swelling ratio test: dry the PBA latex, weigh the PBA (denoted as A), soak the PBA in toluene to swell it, filter it after 24 hours, and weigh the mass of the swollen body (denoted as B);
[0086] Swelling ratio = B / A.
[0087] Table 1 Test results of PBA performance parameters prepared in Examples and Comparative Examples
[0088] Molecular weight Mw Molecular weight distribution Swelling ratio Example 1 20w 1.12 30 Example 2 22w 1.16 35 Example 3 20w 1.09 31 Comparative Example 1 18w 1.1 22 Comparative Example 2 12w 2.93 14 Comparative Example 3 10w 2.45 11
[0089] ASA resin preparation example
[0090] The ASA rubber powder was prepared by using the PBA latex prepared in Examples 1-3 and Comparative Examples 1-3, and was blended with the SAN resin and extruded and injection molded into ASA resin test specimens. The specific steps are as follows:
[0091] 1) Preparation of ASA latex
[0092] 60 kg (by solid content) of polybutyl acrylate latex, 120 kg of deionized water, 0.001 kg of FeSO4·7H2O, 0.01 kg of sodium pyrophosphate, and 0.1 kg of glucose were added to the reactor respectively and stirring was started. After the reactor was heated to 70° C., a mixed pre-emulsion consisting of 0.2 kg of cumene hydroperoxide, 30 kg of styrene, 10 kg of acrylonitrile, 0.5 kg of tert-dodecyl mercaptan, 2.5 kg of potassium oleate and 10 kg of deionized water was continuously added thereto. The continuous feeding time was 3 hours. After the feeding was completed, the reactor was heated to 80° C. and the reaction was continued for 3 hours, then cooled to room temperature and stirring was stopped, and filtered to obtain ASA grafted latex.
[0093] 2) Preparation of ASA rubber powder
[0094] Add 2kg MgSO4 and 200kg deionized water into the coagulation kettle and start stirring to fully dissolve MgSO4, heat the coagulation kettle to 75°C, and add 100kg of the ASA grafted latex prepared in step 1) into the coagulation kettle in a continuous feeding manner for 1 hour. After the feeding is completed, heat the coagulation kettle to 90°C and keep it warm for 1 hour, then cool the coagulation slurry to room temperature for filtering, washing and dehydration to obtain ASA wet rubber powder, and dry the ASA wet rubber powder in a fluidized bed dryer at 65°C to a moisture content of <1% to obtain ASA rubber powder.
[0095] 3) ASA resin preparation and injection molding
[0096] A twin-screw extruder was used, and the three-stage temperatures were 190° C., 210° C. and 220° C. respectively. SAN resin with the brand name SA 30 of LG Chemical was used as the blending continuous phase, and the ASA rubber powder prepared in step 2) was used as the blending dispersed phase. The ASA resin was obtained by blending, extruding and granulating according to the polybutyl acrylate rubber content of 24%.
[0097] The above ASA resin was used to prepare various test specimens at 210°C on an injection molding machine, and its properties were tested according to the following method. The results are shown in Table 2:
[0098] Impact strength value: obtained by testing according to ASTM D2560 standard.
[0099] ASA grafting rate test: Weigh a certain amount of ASA rubber powder (recorded as C), put the rubber powder into acetone and heat it to boil for 2 hours, centrifuge to separate the upper clear liquid and the lower precipitate, and record the dry basis weight of the lower precipitate (recorded as D);
[0100] Grafting rate = (DC*formulation rubber percentage) × % / (C*formulation rubber percentage).
[0101] Izod notched impact: standard ASTM D256, 23°C, using Italian CEAST 9050.
[0102] UV aging performance test: standard GB / T 16422.3-2022, light source: UVA-340nm, irradiance: 0.76W / m2.nm60℃, cycle conditions: illumination 8h, condensation at 50℃ for 4h.
[0103] Table 2 Performance test results of ASA resin prepared in Examples and Comparative Examples
[0104]
[0105]
[0106] It can be seen from the test results of Examples 1-3 and Comparative Examples 1-3 that the PBA rubber prepared by the present invention has a higher molecular weight, a narrower molecular weight distribution, a larger swelling ratio, and can laterally exhibit a higher degree of branching. The ASA resin prepared therefrom has ultrahigh impact strength and excellent weather resistance, with an impact strength greater than 400 J / m, and a dE less than 15 after a UV aging test of 500 h.
[0107] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A method for preparing polybutyl acrylate, characterized in that: The steps include: S1: mixing butyl acrylate, RAFT agent, emulsifier, optional electrolyte and water, and then adding initiator and reducing agent to react to obtain PBA seed emulsion; S2: mixing butyl acrylate, RAFT agent, emulsifier, initiator and water into a pre-emulsion; S3: adding a reducing agent and a pre-emulsion to the PBA seed emulsion to react and prepare polybutyl acrylate.
2. The preparation method according to claim 1, characterized in that: Based on 100 parts of butyl acrylate added in step S1 and step S2, the raw material composition by weight is as follows: Step S1 comprises: 1-10 parts of butyl acrylate, 0.01-0.5 parts of RAFT agent, 0.003-0.1 parts of emulsifier, 0-1 parts of electrolyte, 50-150 parts of water, 0.01-0.05 parts of initiator, and 0.2-1.5 parts of reducing agent; Step S2 comprises: 90-99 parts of butyl acrylate, 5-10 parts of RAFT agent, 0.15-3 parts of emulsifier, 0.1-10 parts of water, and 0.15-3 parts of initiator; Step S3 includes: 0.1-10 parts of reducing agent.
3. The preparation method according to claim 1, characterized in that: The RAFT agent is selected from thioester compounds, preferably one or more of Bis-MPA-RAFT dendrimer, pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothiothio)-2-methylpropanoate, 2-((((2-(((dodecylthio)thiothio)thio)-2-methylpropanoyl)oxy)methyl)-2-methylpropane-1,3-diylbis((2-(((dodecylthio)thiocarbonyl)thio)-2-methylpropanoate).
4. The preparation method according to claim 1, characterized in that: The emulsifier is an anionic emulsifier, preferably one or more of potassium oleate, potassium disproportionate rosin acid, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and dioctyl sodium sulfosuccinate; and / or The electrolyte is an inorganic salt, preferably one or more of potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, and sodium tripolyphosphate; and / or The initiator is selected from inorganic peroxides and / or organic peroxides, preferably one or more of potassium persulfate, sodium persulfate, ammonium persulfate, dicumyl peroxide, and cumyl hydroperoxide; and / or The reducing agent is selected from one or more of ferrous sulfate, glucose, sodium pyrophosphate, disodium ethylenediaminetetraacetate, and bleaching agent.
5. The preparation method according to claim 1, characterized in that: The reaction in step S1 is carried out at a temperature of 50-80°C and a time of 0.3-1h.
6. The preparation method according to claim 1, characterized in that: The pre-emulsion in S3 is added by continuous dripping for 2-5 hours; and / or The reaction in S3 is carried out at a temperature of 50-80°C and a time of 0.5-3h.
7. A polybutyl acrylate, characterized in that Prepared by the method described in any one of claims 1 to 6; Optionally, the product prepared by the method described in any one of claims 1 to 6 is a PBA latex.
8. Use of the polybutyl acrylate described in claim 7 for preparing ASA resin.
9. An ASA resin, characterized in that The ASA rubber powder is obtained by grafting the polybutyl acrylate latex described in claim 7 with styrene and acrylonitrile, agglomerating, dehydrating and drying, and then blending and extruding with SAN resin.
10. The application of the ASA resin according to claim 9 in the fields of home appliances, office supplies and automobiles, especially in the field of automobiles.
Citation Information
Patent Citations
Process of preparing polybutyl acrylate with narrow molecular weight distribution
CN101020729A
Preparing method of acrylonitrile-styrene-acrylic ester tough resin based on segmented copolymer
CN104945763A
Synthesis method of ASA
CN111647246A
Efficient and green free radical polymerization method without inert gas protection
CN115160464A
Cited By
Method for preparing low-temperature-resistant ASA (acrylonitrile-styrene-acrylate) resin by continuous bulk process
CN122188060A